Dramatica : - Phillips, Melanie Anne (Write brothers press, 2001)
Dramatica: A New Theory of Story is the definitive guide to the most profoundly original and complete paradigm of story since Aristotle wrote Poetics. This book is chock-full of stunning solutions to vexing story structure and development problems that have mystified and tormented writers for ages. An absolute must read for any writer who wants to elevate the quality of their written work.